Moving ppportunities: The impact of public housing regenerations on student achievement - Lorenzo Neri (Queen Mary University of London, School of Economics and Finance, 2020)
Neighborhoods can considerably affect children's future outcomes, but the forces through which they operate are not well understood yet. I study how local schools affect the educational achievement of low-income students when their neighborhood changes as a result of an inflow of more affluent households. I use public housing regenerations in London as a natural experiment which caused little displacement of local families and changed the composition of more deprived neighborhoods. I built a novel database by geocoding all regenerations and linking them to administrative records on primary school-age students. I compare the achievement of students in schools of the same neighborhood but located at different distances from the regeneration before and after its completion, and estimate the impact on students who were originally enrolled in local schools before completion. Such students have higher test scores at the end of primary school after the regeneration. Gains are stronger for more disadvantaged and low-ability students. The empirical evidence suggests that such gains are driven by changes in the demand for schools due to the inflow of more affluent parents with strong preferences for school quality.
Keywords: I21; I38; R23; 330; Neighborhood effects; Public housing programs; Student achievement